Pretreatment of Human Umbilical Cord Mesenchymal Stem Cell-Derived Exosomes with Quercetin Enhances the Healing of Diabetic Skin Wounds by Modulating Host-Microbiota Interactions - Wu S; Zhou Z; Li Y; Wu R; Jiang J (International Journal of Nanomedicine)
Shuhui Wu,1,* Zhongsheng Zhou,1,* Yang Li,1 Ronghui Wu,2 Jinlan Jiang1 1Scientific Research Center, China-Japan Union Hospital of Jilin University, Changchun, People’s Republic of China; 2Department of Dermatology, China-Japan Union Hospital of Jilin University, Changchun, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jinlan Jiang, Scientific Research Center, China-Japan Union Hospital of Jilin University, Changchun, Jilin, 130033, People’s Republic of China, Email jiangjinlan@jlu.edu.cnBackground: Owing to the distinctive advantages of mesenchymal stem cell-derived exosomes (MSCs-exo), these vesicles have emerged as a pivotal research focus in regenerative medicine, surpassing their MSC counterparts. Quercetin (Qr), widely recognized for its potent anti-inflammatory and antioxidant activities, demonstrates substantial potential in enhancing tissue repair processes. This study delves into the role of quercetin-pretreated MSC-derived exosomes (MSCsQr-exo) in accelerating the healing of diabetic wounds.Methods: MSCsQr-exo were isolated from quercetin-pretreated MSCs and applied to fibroblasts to evaluate changes in cell function. An in vitro DSW rat model was also developed, and the rats were treated with MSCsQr-exo to assess wound healing progression. Fecal samples were collected for 16S rRNA sequencing and untargeted metabolomics to analyze changes in gut microbiota and metabolic profiles.Results: MSCsQr-exo significantly enhanced fibroblast proliferation and migration while improving the therapeutic efficacy of MSCs-exo in DSW treatment. Gut microbiota and metabolomic analyses revealed marked changes in DSW rats, with MSCsQr-exo effectively alleviating dysbiosis. MSCsQr-exo upregulated Faecalibacterium abundance and regulated arachidonic acid metabolism in both the arachidonic and linoleic acid pathways. Firmicutes and Enterobacteriaceae influenced the arachidonic acid pathway by modulating 14.15-EET expression levels.Conclusion: MSCsQr-exo facilitate DSW wound healing through modulation of dysbiotic gut microbiota linked to DSW pathology. This discovery offers novel therapeutic avenues and research trajectories for enhancing DSW recovery. Keywords: mesenchymal stem cells, exosomes, quercetin, diabetic skin wound, gut microbiota, metabolites